2020
DOI: 10.3390/sym12020189
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Implementation and Design of a Hybrid Chaos-AES Color Image Encryption Algorithm

Abstract: In this paper, we propose an image encryption algorithm based on four-dimensional chaotic system to generate key and improve advanced encryption standard. The encryption algorithm is optimized by using the pipeline and parallel computing features of Field Programmable Gate Array (FPGA). First, the chaotic system is used as a key generator for the encryption algorithm. Next, in the improved advanced encryption standard, ShiftRows and SubByres are modified with Spin-Sort and Cubic S-Box, and the round of encrypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Block encryption algorithms are ineffective in the encryption of digital images. One of the most important reasons for this problem is the high correlation between the pixel values of an image [38]. Usually, images are represented by a matrix with a size of m × n .…”
Section: Detail Of Proposed Methodsmentioning
confidence: 99%
“…Block encryption algorithms are ineffective in the encryption of digital images. One of the most important reasons for this problem is the high correlation between the pixel values of an image [38]. Usually, images are represented by a matrix with a size of m × n .…”
Section: Detail Of Proposed Methodsmentioning
confidence: 99%
“…Yang, Cheng, et al [58] proposed a four-dimensional chaotic method to produce keys and boost the Advanced Encryption Standard. Using FPGA pipelines and parallel processing, the encryption algorithm is simplified as the secret to the encryption algorithm is the chaotic process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A combined-block strategy employing Key Expansion design for improving the throughput and for minimizing the power usage was introduced by Kalaiselvi [22]. In numerous additional scientific studies [23][24][25][26][27], various degrees of pipelined architectures were suggested. Granado et al [28] created a high-speed AES formula execution for Wi-FI Protected Access 2 (WPA2) systems.…”
Section: Literature Reviewmentioning
confidence: 99%